Comprehensive RNAseq analysis for identification of genes expressed under heat stress in lentil. Issue 4 (25th April 2021) - Kumar, Jitendra; Gupta, Debjyoti Sen; Kesari, Ravi; Verma, Renu; Murugesan, Senthilkumar; Basu, Partha Sarathi; Soren, Khela Ram; Gupta, Sanjeev; Singh, Narendra Pratap
Abstract: Lentils are highly sensitive to abrupt increases in temperature during the mid to late reproductive stages, leading to severe biomass and seed yield reduction. Therefore, we carried out an RNAseq analysis between IG4258 (heat tolerant) and IG3973 (heat sensitive) lentil genotypes at the reproductive stage under both normal and heat stress conditions in the field. It resulted in 209, 549 assembled transcripts and among these 161, 809 transcripts had coding regions, of which 94, 437 transcripts were annotated. The differential gene expression analysis showed upregulation of 678 transcripts and downregulation of 680 transcripts between the tolerant and sensitive genotypes at the early reproductive stage. While 76 transcripts were upregulated and 47 transcripts were downregulated at the late reproductive stage under heat stress conditions. The validation of 12 up‐or downregulated transcripts through RT‐PCR corresponded well with the expression analysis data of RNAseq, with a correlation of R 2 = 0.89. Among these transcripts, the DN364_c1_g1_i9 and DN2218_c0_g1_i5 transcripts encoded enzymes involved in the tryptophan pathway, indicating that tryptophan biosynthesis plays a role under heat stress in lentil. Moreover, KEGG pathways enrichment analysis identified transcripts associated with genes encoding proteins/regulating factors related to different metabolic pathways including signal transduction, fatty acid biosynthesis, rRNA processing, ribosome biogenesis, gibberellin (GA) biosynthesis, and riboflavin biosynthesis. This analysis also identified 6852 genic‐SSRs leading to the development of 4968 SSR primers that are potential genomic resources for molecular mapping of heat‐tolerant genes in lentil.